Dental Machining Composites
By using hygroscopic polymers, low viscosity polymers and glass fiber cloth in dental cutting composites, the filling rate and texture method are adjusted, and the strength problem of existing dental cutting composites under multi-directional stress is solved, and the high strength and modulus of the dental frame are achieved is achieved.
Patent Information
- Application Number
- JP2024524750
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-27
- Filing Date
- 2024-02-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Existing dental cutting composite materials are difficult to efficiently process in CAD/CAM systems, and it is difficult to meet the strength requirements of dental frames under multi-directional stress.
A photocurable resin containing hygroscopic polymer and low viscosity polymer is used, combined with an appropriate glass fiber cloth, and by adjusting the filling rate and texture of the glass fiber cloth, a dental cutting composite material with excellent three-point bending strength and modulus is prepared.
The high strength and modulus of the dental frame are achieved and the modulus is close to the teeth, and the performance of dental cutting composite materials under multi-directional stress is improved, which is suitable for efficient processing of dental frames.
Smart Images

Figure 0007656996000001 
Figure 0007656996000002 
Figure 0007656996000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite material for dental cutting. [Background technology]
[0002] When performing dental treatment for missing teeth, glass fiber reinforced composite materials, which are a combination of resin and glass fiber (glass fiber), may be used. The shape of the glass fiber referred to here can be straight, with glass fibers aligned in one direction, or woven with glass fibers. For example, straight glass fibers are used in rod-shaped glass fiber reinforced composite materials called fiber cores, which are used in root canal treatment. In prosthetic treatment, when one or two teeth are missing, a prosthesis (bridge) consisting of three or four artificial teeth connected to bridge the remaining abutment teeth on both sides may be used, and the glass fiber reinforced composite material used in the frame part of the bridge contains both straight glass fiber and woven glass fiber. For example, the shape of the glass fiber is differentiated by the straight glass fiber, which is particularly excellent in strength from a single direction, used for the bridge part between the abutment teeth, and the woven glass fiber, which is excellent in strength from multiple directions, used for the abutment coping part that covers the abutment teeth. Glass fiber reinforced composite materials such as these are used as reinforcing materials in root canal treatment and prosthetic treatment when the strength of resin alone is insufficient. The frame referred to here is the abutment coping, which is the base that covers the abutment tooth, or a structure in which multiple abutment copings are connected together, and the surface of the abutment coping is covered with dental resin, dental porcelain, etc. to produce the prosthesis. Traditionally, the materials used for frames have generally been metals (such as gold-silver-palladium alloys) or ceramics (such as zirconia). In recent years, however, glass fiber reinforced composite materials, which combine flexibility, strength, and lightness, have begun to be used in the above-mentioned dental treatments.
[0003] Traditionally, dental prostheses were made entirely by hand, but in recent years, mechanization has progressed with the spread of CAD / CAM (Computer-Aided design / Computer-Aided Manufacturing) systems. With this system, dental prostheses can be obtained by cutting rectangular prisms, cylinders, disks, and other objects to be cut using a cutting machine.
[0004] Here, JIS T 6526 (dental ceramic materials) requires that the bending strength of a three-tooth connected prosthesis is 500 MPa or more. In addition, since the elastic modulus of human dentin and human enamel is approximately 18 GPa and approximately 84 GPa, respectively, it is considered desirable that the elastic modulus of the frame part is close to the elastic modulus of tooth tissue (18 to 84 GPa). By setting the elastic modulus of the frame part to 18 GPa to 84 GPa, the deformation or shock absorber (shock absorption) of the material against the stress caused by occlusion becomes the same as that of tooth tissue, reducing the load on the dental prosthesis and tooth root, and reducing the risk of them breaking.
[0005] For example, the following fiber-reinforced composite materials have been proposed for dental use: Patent Document 1 describes a dental mill blank for cutting, which contains a polymer (A) and inorganic long fibers (B), the inorganic long fibers (B) being oriented in one direction. The initial three-point bending strength of this dental mill blank is 700 MPa or more, which satisfies the 500 MPa or more required for the three-point bending strength of a three-tooth connected prosthesis in JIS T 6526. However, the dental mill blank described in Patent Document 1 contains glass fibers that are not woven but straight and oriented in one direction, so the strength of the glass fibers in the long axis direction (extension direction) is high. However, the strength of the glass fibers in the radial direction (perpendicular to the long axis direction) is thought to be significantly lower than that in the long axis direction of the glass fibers. In the oral cavity, stress is applied to the abutment coping that is placed on the abutment tooth of the frame from various directions, not just the long axis direction of the glass fibers. Therefore, the dental mill blank described in Patent Document 1 is not suitable for producing the entire frame including the abutment coping.
[0006] Patent document 2 describes a block-shaped composite material for dental cutting, which has a multilayer structure including at least two layers with different transparency, and in which the layers contain a curable resin and a fiber material, characterized in that the fiber material is a sheet (woven fabric) made of long fiber material. However, only the contrast ratio is evaluated in the examples of Patent Document 2, and the mechanical properties of the dental cutting block composite material are unknown. Since the glass fiber is woven, the strength in multiple directions is excellent, but the amount of glass fiber in one direction is small. For example, in a plain weave with the same number of warp and weft threads, the number in one direction is half, so it is assumed that the reinforcing effect in one direction is reduced to about half. In other words, it is considered difficult for the dental cutting block composite material described in Patent Document 2, which contains glass fiber fabric, to achieve a three-point bending strength of 500 MPa or more, as with the dental mill blank (425 MPa) containing woven (cross-shaped) glass fiber and polymer resin in the comparative example of Patent Document 1. Therefore, there is a need to develop a composite material for dental cutting that is suitable for producing dental frames that has excellent three-point bending strength and a three-point bending modulus close to that of tooth structure. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2020 / 166667 [Patent Document 2] Patent No. 5944602 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention aims to provide a composite material for dental cutting that can be cut using a CAD / CAM system and is suitable for producing dental frames having excellent three-point bending strength and a three-point bending modulus close to that of tooth structure. [Means for solving the problem]
[0009] As a result of intensive research into solving the above problems, the inventors discovered that in a composite material for dental cutting containing a curable resin and a glass fiber fabric, the above object can be achieved by impregnating the glass fiber fabric with a polymerizable monomer-containing composition of a specific viscosity and adjusting the filling rate of the glass fiber fabric, thereby completing the present invention.
[0010] That is, the present invention is as follows. Section 1. A dental cutting composite material comprising a hardenable resin and a glass fiber fabric, The curable resin is (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator A polymerizable monomer-containing composition comprising the above is polymerized and cured, the (B) low-viscosity polymerizable monomer is a polymerizable monomer having a viscosity of 5 mPa s or less at 31°C, The viscosity of the mixture of the (A) polyfunctional (meth)acrylate polymerizable monomer and the (B) low-viscosity polymerizable monomer at 31° C. is 8 to 2300 mPa s, and The filling rate of the glass fiber fabric in the dental cutting composite material is 48 to 80 mass%. Composite materials for dental cutting. Section 2. Item 1. A composite material for dental cutting according to item 1, having a three-point bending strength of 500 MPa or more. Section 3. Item 1. A composite material for dental cutting according to item 1, having a three-point bending modulus of 18 to 36 GPa. Section 4. Item 2. The composite material for dental cutting according to item 1, wherein the (A) polyfunctional (meth)acrylate-based polymerizable monomer is selected from the group consisting of a di(meth)acrylate containing bisphenol A, a urethane di(meth)acrylate which is a reaction product of 2 moles of a (meth)acrylate having a hydroxyl group and 1 mole of a diisocyanate, a tri(meth)acrylate, and a tetra(meth)acrylate. Section 5. Item 2. The composite material for dental cutting according to item 1, wherein the (B) low viscosity polymerizable monomer comprises at least one selected from the group consisting of methacrylic acid, diethylene glycol dimethacrylate, and triethylene glycol dimethacrylate. Section 6. Item 2. The composite material for dental cutting according to item 1, wherein the content of the (B) low viscosity polymerizable monomer in the polymerizable monomer-containing composition is 5 to 150 parts by mass relative to 100 parts by mass of the (A) polyfunctional (meth)acrylate-based polymerizable monomer. Section 7. Item 2. The composite material for dental cutting according to item 1, wherein the content of the polymerization initiator (C) in the polymerizable monomer-containing composition is 0.002 to 5 parts by mass per 100 parts by mass of the polyfunctional (meth)acrylate-based polymerizable monomer (A) and the low-viscosity polymerizable monomer (B). Section 8. Item 1. A composite material for dental cutting as described in item 1, used as a frame. Section 9. The dental cutting composite material comprises: (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator Item 2. The composite material for dental cutting according to item 1, which is a glass fiber fabric impregnated with a polymerizable monomer-containing composition comprising the polymerizable monomer, and polymerized and cured. Section 10. A method for producing a composite material for dental cutting, comprising: (1) placing at least one sheet of woven glass fabric into a mold cavity; (2) impregnating the glass fiber fabric with a polymerizable monomer-containing composition; and (3) A step of polymerizing and curing the polymerizable monomer-containing composition to obtain a composite material for dental cutting containing a curable resin and a glass fiber fabric. A manufacturing method comprising: Section 11. Item 11. The method for producing a composite material for dental cutting according to item 10, wherein in step (1), the at least one piece of glass fiber fabric is placed so that the thickness direction of the glass fiber fabric is parallel or perpendicular to the bottom surface of the mold. Section 12. Item 12. The method for producing a composite material for dental cutting according to item 11, characterized in that in step (2), the polymerizable monomer-containing composition is poured in a direction parallel or perpendicular to the thickness direction of the glass fiber fabric. Section 13. Item 11. The method for producing a composite material for dental cutting according to item 10, wherein the glass fiber fabric is a glass fiber fabric laminate of at least two layers. Section 14. Item 14. The method for producing a composite material for dental cutting according to item 13, characterized in that in step (1), the glass fiber woven laminate is placed so that the lamination direction of the glass fiber woven fabric is parallel or perpendicular to the bottom surface of the mold. Section 15. Item 15. The method for producing a composite material for dental cutting according to item 14, characterized in that in step (2), the polymerizable monomer-containing composition is poured from a direction perpendicular to the lamination direction of the glass fiber woven fabric laminate. Section 16. (1) placing at least one sheet of woven glass fabric into a mold cavity; (2) impregnating the glass fiber fabric with a polymerizable monomer-containing composition; and (3) A step of polymerizing and curing the polymerizable monomer-containing composition to obtain a composite material for dental cutting containing a curable resin and a glass fiber fabric. A composite material for dental cutting, comprising a curable resin and a glass fiber fabric, the composite material being obtained by a manufacturing method comprising the steps of: Section 17. 1. Use of a composition containing a hardenable resin and a glass fiber fabric as a composite material for dental cutting, comprising: The curable resin is (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator A polymerizable monomer-containing composition comprising the above is polymerized and cured, the (B) low-viscosity polymerizable monomer is a polymerizable monomer having a viscosity of 5 mPa s or less at 31°C, The viscosity of the mixture of the (A) polyfunctional (meth)acrylate polymerizable monomer and the (B) low-viscosity polymerizable monomer at 31° C. is 8 to 2300 mPa s, and The filling rate of the glass fiber fabric in the dental cutting composite material is 48 to 80 mass%. Use as a composite material for dental cutting. Section 18. The dental cutting composite material comprises: (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator Item 18. The use as a composite material for dental cutting according to item 17, wherein the glass fiber fabric is impregnated with a polymerizable monomer-containing composition comprising the polymerizable monomer and cured by polymerization.
[0011] In addition, in the present invention, the composite material for dental cutting defined by the manufacturing process is described as a product-by-process claim because it is impossible or impractically difficult to specify at present what components it contains or what its structure is. Effect of the Invention
[0012] According to the present invention, in a composite material for dental cutting containing a curable resin and a glass fiber fabric, by using a glass fiber fabric that has a reinforcing effect in multiple directions and adjusting its filling rate, a composite material for dental cutting suitable for producing dental frames having excellent three-point bending strength and a three-point bending modulus close to that of tooth tissue can be obtained by a CAD / CAM system. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The composite material for dental cutting of the present invention has a unitary structure containing a hardenable resin and a glass fiber fabric.
[0014] hardening resin The hardenable resin contained in the composite material for dental cutting of the present invention is (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator The polymerizable monomer-containing composition is polymerized and cured. As described later, the dental cutting composite material of the present invention can contain a curable resin by polymerizing and curing a polymerizable monomer-containing composition containing (A) a polyfunctional (meth)acrylate-based polymerizable monomer and (B) a low-viscosity polymerizable monomer. The polymerizable monomer-containing composition may also be referred to as "(D)" or "component D".
[0015] (A) Polyfunctional (meth)acrylate-based polymerizable monomer In the present invention, a polyfunctional (meth)acrylate polymerizable monomer (hereinafter, sometimes referred to as "Component A") is used as a polymerizable monomer constituting a structural unit of the curable resin. Note that (meth)acrylate means acrylate or methacrylate. The polyfunctional (meth)acrylate polymerizable monomer is a monomer used for the purpose of imparting high strength to a composite material for dental cutting.
[0016] The polyfunctional (meth)acrylate polymerizable monomer may be a polyfunctional (meth)acrylate polymerizable monomer that is usable for dental use and has a viscosity of more than 5 mPa·s at 31° C. The viscosity of the polyfunctional (meth)acrylate polymerizable monomer at 31° C. is preferably in the range of 10 to 200,000 mPa·s, and more preferably in the range of 30 to 180,000 mPa·s. Examples of such polyfunctional (meth)acrylate polymerizable monomers include di(meth)acrylates such as bisphenol A-containing di(meth)acrylates, and urethane di(meth)acrylates which are reaction products of 2 moles of a (meth)acrylate having a hydroxyl group with 1 mole of a diisocyanate; tri(meth)acrylates such as trimethylolpropane tri(meth)acrylate; and tetra(meth)acrylates such as pentaerythritol tetra(meth)acrylate.
[0017] Examples of the polyfunctional (meth)acrylate include bisphenol A di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, ethylene oxide modified bisphenol A glycidyl di(meth)acrylate, 2,2-bis(4-methacryloxypropoxyphenyl)propane, 7,7,9-trimethyl-4,13-dioxa-3,14-dioxo-5,12-diazahexadecane-1,16-diol di(meth)acrylate, and neopentyl glycol hydroxypivalic acid esther. Terephthalic acid di(meth)acrylate, caprolactone-modified hydroxypivalic acid neopentyl glycol ester di(meth)acrylate, trimethylolethane di(meth)acrylate, trimethylolpropane di(meth)acrylate, urethane di(meth)acrylate (1,6-bis((meth)acryloyloxy-2-ethoxycarbonylamino)-2,4,4-trimethylhexane), reaction product of 3-chloro-2-hydroxypropyl (meth)acrylate with methylcyclohexane diisocyanate , reaction products of 2-hydroxypropyl (meth)acrylate and methylcyclohexane diisocyanate, reaction products of 2-hydroxypropyl (meth)acrylate and methylenebis(4-cyclohexylisocyanate), reaction products of 2-hydroxypropyl (meth)acrylate and trimethylhexamethylene diisocyanate, reaction products of 2-hydroxyethyl (meth)acrylate and isophorone diisocyanate, reaction products of 3-chloro-2-hydroxypropyl (meth)acrylate and isophorone diisocyanate Examples of the di(meth)acrylate include a reaction product with an isocyanate; a tri(meth)acrylate such as trimethylolmethane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate; and a tetra(meth)acrylate such as pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate.
[0018] The polyfunctional (meth)acrylate polymerizable monomer is preferably trimethylolpropane trimethacrylate (TMPTMA), urethane dimethacrylate (UDMA), bisphenol A glycidyl dimethacrylate (Bis-GMA), or ethoxylated bisphenol A dimethacrylate (Bis-EMA), and more preferably UDMA or Bis-EMA.
[0019] These polyfunctional (meth)acrylate polymerizable monomers can be used alone, but two or more types of polyfunctional (meth)acrylate polymerizable monomers may be used in combination. The molecular weight of the polyfunctional (meth)acrylate polymerizable monomer is not particularly limited, and may be, for example, in the range of 300 to 10,000.
[0020] The content of the polyfunctional (meth)acrylate polymerizable monomer contained in the polymerizable monomer-containing composition is preferably from 40 to 95% by mass, and more preferably from 50 to 80% by mass.
[0021] In addition, the curable resin contained in the dental cutting composite material of the present invention can be polymerized by mixing other polymerizable monomers other than the above-mentioned polyfunctional (meth)acrylate polymerizable monomers in order to adjust the viscosity, polymerizability, or other physical properties, in addition to the above-mentioned polyfunctional (meth)acrylate polymerizable monomers.
[0022] (B) Low viscosity polymerizable monomer The low-viscosity polymerizable monomer is a monomer used for the purpose of adjusting the viscosity of the polymerizable monomer-containing composition to be impregnated into the glass fiber fabric and increasing the impregnation property. The low-viscosity polymerizable monomer acts as a diluent for the (A) polyfunctional (meth)acrylate polymerizable monomer, i.e., has the effect of reducing the viscosity, and is a monomer that can be mixed with the (A) polyfunctional (meth)acrylate polymerizable monomer. The low-viscosity polymerizable monomer may be a polymerizable monomer having a low viscosity, for example, a viscosity of 5 mPa·s or less at 31° C. The viscosity of the low-viscosity polymerizable monomer at 31° C. is preferably in the range of 0.01 to 4.5 mPa·s, and more preferably in the range of 0.1 to 4.9 mPa·s. Examples of low-viscosity polymerizable monomers include methacrylic acid (viscosity: less than 0.3 mPa·s (31°C), less than 1.34 mPa·s (25°C)), diethylene glycol dimethacrylate (DEGDMA) (viscosity: 3 mPa·s (31°C), less than 5 mPa·s (25°C)), triethylene glycol dimethacrylate (TEGDMA) (viscosity: 5 mPa·s (31°C), less than 9 mPa·s (25°C)), acrylic acid (viscosity: 1.3 mPa·s (20°C)), methyl acrylate (viscosity: 0.482 mPa·s (21°C)), ethyl acrylate (viscosity: 0.535 mPa·s (25°C)), 1,6-hexanediol diacrylate (viscosity: 6 mPa·s (25°C)), neopentyl glycol diacrylate (viscosity: 1.5 mPa·s (20°C)), and ethyl acrylate (viscosity: 0.535 mPa·s (25°C)). Examples include methacrylate (viscosity: 6 mPa·s (25°C)), methyl methacrylate (viscosity: 0.56 mPa·s (20°C)), ethyl methacrylate (viscosity: 1 mPa·s or less (25°C)), methoxydiethylene glycol methacrylate (viscosity: 2 mPa·s (25°C)), methoxytetraethylene glycol methacrylate (viscosity: 7 mPa·s (25°C)), phenoxyethylene glycol methacrylate (viscosity: 7 mPa·s (25°C)), ethylene glycol dimethacrylate (viscosity: 3.2 mPa·s (20°C)), 1,6-hexanediol dimethacrylate (viscosity: 6 mPa·s (25°C)), and neopentyl glycol dimethacrylate (viscosity: 5 mPa·s (25°C)). These have a short molecular length, which also has the effect of increasing the polymerization rate during hardening. As the low viscosity polymerizable monomer, methacrylic acid, diethylene glycol dimethacrylate, and triethylene glycol dimethacrylate are preferred. These low viscosity polymerizable monomers can be used alone, but two or more kinds of low viscosity polymerizable monomers may be used in combination. The molecular weight of the low-viscosity polymerizable monomer is not particularly limited, and may be, for example, in the range of 30 to 10,000.
[0023] The content of the (B) low-viscosity polymerizable monomer in the polymerizable monomer-containing composition is usually 5 to 150 parts by mass, preferably 10 to 100 parts by mass, more preferably 20 to 70 parts by mass, and further preferably 30 to 50 parts by mass, based on 100 parts by mass of the (A) polyfunctional (meth)acrylate polymerizable monomer.
[0024] The viscosity at 31° C. of a polymerizable monomer mixture containing (A) a polyfunctional (meth)acrylate polymerizable monomer and (B) a low-viscosity polymerizable monomer, but not containing (C) a polymerization initiator, is usually 8 to 2300 mPa·s, preferably 15 to 1000 mPa·s, and more preferably 25 to 150 mPa·s. By controlling the viscosity of the polymerizable monomer mixture within the above range, molding defects caused by significant shrinkage of the polymerizable monomer-containing composition during polymerization and curing can be prevented, and a high-strength composite material for dental cutting can be obtained by thoroughly impregnating a glass fiber fabric with the polymerizable monomer-containing composition. The viscosity of (A) the polyfunctional (meth)acrylate-based polymerizable monomer, (B) the low-viscosity polymerizable monomer, and the polymerizable monomer mixture can be determined by measurement at 31°C using an SV-type (tuning-fork vibration type) viscometer or a B-type (rotational type) viscometer.
[0025] The combination of the polyfunctional (meth)acrylate-based polymerizable monomer (A) and the low-viscosity polymerizable monomer (B) is not particularly limited, and examples thereof include A combination of 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (UDMA) and methacrylic acid (MAA), A combination of ethoxylated bisphenol A dimethacrylate (Bis-EMA) and MAA, A combination of UDMA, Bis-EMA and MAA; A combination of UDMA, MAA, and diethylene glycol dimethacrylate (DEGDM); A combination of Bis-EMA, MAA, and DEGDM, A combination of UDMA, Bis-EMA, MAA and DEGDM; A combination of UDMA, MAA, and triethylene glycol dimethacrylate (TEGDM); Combination of Bis-EMA, MAA and TEGDM, A combination of UDMA, Bis-EMA, MAA and TEGDM; A combination of UDMA, DEGDM, and TEGDM, A combination of Bis-EMA, DEGDM, and TEGDM, A combination of UDMA, Bis-EMA, DEGDM and TEGDM; A combination of UDMA and DEGDM, Combination of Bis-EMA and DEGDM, A combination of UDMA, Bis-EMA and DEGDM; Combination of UDMA and TEGDM Combination of Bis-EMA and TEGDM Examples include a combination of UDMA, Bis-EMA, and TEGDM.
[0026] (C) Polymerization initiator In the composite material for dental cutting of the present invention, a polymerization initiator is used to polymerize and harden (A) the polyfunctional (meth)acrylate polymerizable monomer and (B) the low-viscosity polymerizable monomer that constitute the hardenable resin.
[0027] The polymerization initiator is not particularly limited as long as it is a commonly used polymerization initiator, and among them, a polymerization initiator used for dental purposes is preferable. Generally, different types of polymerization initiators are used depending on the polymerization means of the polymerizable monomer. For example, when the polymerization means is light irradiation, a photopolymerization initiator is used, and when the polymerization means is heat treatment, a thermal polymerization initiator is used.
[0028] The photopolymerization initiator is not particularly limited, and a photopolymerization initiator that reacts with ultraviolet light or visible light to generate radicals can be used.Specific examples include α-diketones such as diacetyl, acetylbenzoyl, benzyl, camphorquinone (CQ), 9,10-phenanthrenequinone, and acenaphthenequinone; benzoin alkyl ethers such as benzoin methyl ether, benzoin ethyl ether, and benzoin propyl ether; thioxanthone compounds such as 2,4-diethylthioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and methylthioxanthone; and benzophenone compounds such as benzophenone, p,p'-dimethylaminobenzophenone, and p,p'-dimethoxyaminobenzophenone.
[0029] The thermal polymerization initiator is not particularly limited, and known thermal polymerization initiators such as peroxides and azo compounds can be used. Specific examples include benzoyl peroxide (BPO), ketone peroxide, peroxyketal, hydroperoxide, dialkyl peroxide, diacyl peroxide, peroxy ester, peroxydicarbonate, 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 4,4'-azobis-4-cyanovaleric acid, 1,1'-azobis-1-cyclohexanecarbonitrile, dimethyl-2,2'-azobisisobutyrate, and 2,2'-azobis-(2-aminopropane)dihydrochloride. These polymerization initiators may be used alone, but two or more of them may be used in combination.
[0030] The content of the polymerization initiator is usually 0.002 to 5 parts by mass, preferably 0.01 to 3 parts by mass, more preferably 0.05 to 1 part by mass, and even more preferably 0.1 to 0.3 parts by mass, based on 100 parts by mass of the total of the (A) polyfunctional (meth)acrylate polymerizable monomer and the (B) low-viscosity polymerizable monomer. By setting the content of the polymerization initiator within the above range, the polymerization initiator can be dissolved in the (A) polyfunctional (meth)acrylate polymerizable monomer and the (B) low-viscosity polymerizable monomer, and the polymerizable monomer-containing composition can be polymerized and cured. Note that even if the amount of the polymerization initiator is very small (0.01 parts by mass or less), the polymerizable monomer-containing composition can be sufficiently cured to obtain a high-strength composite material for dental cutting processing.
[0031] In addition to the above-mentioned polymerization initiator, a polymerization promoter can be used in combination for the polymerization of the polymerizable monomer used in the present invention. The polymerization accelerator is generally used in combination with a photopolymerization initiator.The polymerization accelerator is not particularly limited, and can be, for example, 2-(dimethylamino)ethyl methacrylate (DMAEMA), 2-(dimethylamino)ethyl methacrylate benzoate (DMABE), 2-(dimethylamino)ethyl methacrylate benzoate n-butoxyethyl, etc.
[0032] Furthermore, the dental cutting composite material of the present invention may contain, as necessary, various other known additives such as inorganic fillers, polymerization accelerators, color pigments, opacifiers, phosphors, opalizing agents, polymerization inhibitors, antioxidants, antibacterial agents, X-ray contrast agents, stabilizers, ultraviolet absorbers, and discoloration inhibitors. These may be used alone or in appropriate combination of two or more.
[0033] Method for producing polymerizable monomer-containing composition The polymerizable monomer-containing composition can be produced by blending and mixing (A) a polyfunctional (meth)acrylate-based polymerizable monomer, (B) a low-viscosity polymerizable monomer, and (C) a polymerization initiator such that the amount of the (C) polymerization initiator is 0.002 to 5 parts by mass per 100 parts by mass of the total of the (A) polyfunctional (meth)acrylate-based polymerizable monomer and the (B) low-viscosity polymerizable monomer.
[0034] The mixing ratio (mixing ratio) of each component in the polymerizable monomer-containing composition can be adjusted appropriately depending on the viscosity and the purpose of use. For example, (A) polyfunctional (meth)acrylate-based polymerizable monomer, (B) low-viscosity polymerizable monomer, and (C) polymerization initiator are mixed so that the (C) polymerization initiator is 0.002 to 5 parts by mass per 100 parts by mass of the total of the (A) polyfunctional (meth)acrylate-based polymerizable monomer and the (B) low-viscosity polymerizable monomer, and additives such as inorganic fillers, polymerization accelerators, coloring pigments, opacifiers, opalizing agents, phosphors, polymerization inhibitors, antioxidants, antibacterial agents, X-ray contrast agents, stabilizers, ultraviolet absorbers, and discoloration inhibitors can be mixed as necessary. Note that the polymerization initiator contained in the monomer-containing composition must be handled with care, and the storage environment must be air-shielded, dark, and low temperature.
[0035] The method for producing the polymerizable monomer-containing composition includes a step of placing a predetermined amount of each of the components in a container, thoroughly kneading the components to uniformly disperse them, thereby obtaining the polymerizable monomer-containing composition.
[0036] Glass fiber fabric The composite material for dental cutting of the present invention contains a glass fiber fabric. The glass fiber fabric may be any known glass fiber fabric used as a dental material without any restrictions. The glass fiber fabric may also be referred to as "(E)" or "E component". Examples of the material of the glass fiber fabric include A-glass, C-glass, D-glass, E-glass, ECR-glass, AR-glass, and S-glass. A-glass means a glass composition containing 72 mass% of SiO2, 0.6 mass% of Al2O3, 10 mass% of CaO, 2.5 mass% of MgO, and 14.7 mass% of Na2O based on the total amount. C-glass means a glass composition containing 65 mass% of SiO2, 14 mass% of Al2O3, 5 mass% of B2O3, 7 to 14 mass% of CaO, 3 mass% of MgO, 8 to 11 mass% of Na2O, and 1 mass% of K2O based on the total amount. D-glass means a glass composition containing, based on the total amount, 74% by mass of SiO2, 0.5% by mass of Al2O3, 22% by mass of B2O3, 0.5% by mass of CaO, 1% by mass of Na2O, 1.5% by mass of K2O, and 0.5% by mass of Li2O. E-glass means a glass composition containing, based on the total amount, 52-56% by mass of SiO2, 12-16% by mass of Al2O3, 0-0.8% by mass of Fe2O3, 0-13% by mass of B2O3, 15-25% by mass of CaO, 0-6% by mass of MgO, a total of 0-2% by mass of Na2O+K2O, 0-1.5% by mass of TiO2, and 0-1% by mass of F2. ECR-glass means a glass composition containing 58.2 mass% SiO2, 11.3 mass% Al2O3, 0.3 mass% Fe2O3, 22 mass% CaO, 2.7 mass% MgO, 0.1 mass% Na2O, 0.5 mass% K2O, 2.2 mass% TiO2, and 2.7 mass% ZnO based on the total amount. AR-glass means a glass composition containing 62.5 mass% SiO2, 0.5 mass% Al2O3, 0-0.8 mass% Fe2O3, 5.7 mass% CaO, 14.2 mass% Na2O, 0.3 mass% K2O, and 16.8 mass% ZrO2 based on the total amount. S-glass means a glass composition containing 65 mass% SiO2, 25 mass% Al2O3, and 10 mass% MgO based on the total amount. Preferred woven glass materials are E-glass, AR-glass, and S-glass.
[0037] The average fiber diameter of the glass fibers is not particularly limited as long as the effects of the present invention are achieved, but is usually 1 to 100 μm, preferably 2 to 20 μm, and more preferably 3 to 15 μm. The average fiber diameter can be determined by electron microscope observation. Specifically, a scanning electron microscope (SEM; for example, "SU3500H-800NA type" manufactured by Hitachi High-Technologies Corporation) image of a cross section perpendicular to the orientation direction of the glass fibers is taken, and the fiber diameters of glass fibers (100 or more) observed within a unit field of view of the SEM image are measured using image analysis type particle size distribution measurement software ("Mac-View" manufactured by Mountec Co., Ltd., etc.), whereby the average fiber diameter of the glass fibers can be determined. At this time, the fiber diameter of the glass fibers is determined as a circle equivalent diameter, which is the diameter of a circle having the same area as the area of the glass fibers, and the average fiber diameter is calculated from the number of glass fibers and their fiber diameters. As the glass fibers, commercially available products having the above average fiber diameter may be used. The average fiber diameter of the glass fibers can also be adjusted by, for example, mixing fibers (for example, commercially available products) having different average fiber diameters.
[0038] Here, the glass fiber fabric has a weave structure in which glass fibers are woven. The weave structure is a structure formed by intersecting and weaving two-directional glass fibers, warp and weft. Straight glass fibers that are not woven have a plurality of glass fibers arranged in one direction, and therefore exhibit very high strength when a load perpendicular to the long axis direction (extension direction) of the fiber is applied, but have a weakness in that they are weak against loads applied parallel to the radial direction (perpendicular to the long axis direction). For this reason, in order to overcome the weakness of straight glass fibers, it is preferable to use a weave structure in which glass fibers are woven into the weft and warp, and which has the advantage of being less susceptible to loads in multiple directions. Representative examples of such weave structures include plain weave, twill weave, satin weave, basket weave, leno weave, mock leno weave, etc., but from the viewpoint of strength and moldability, plain weave and twill weave are preferred. In plain weave, the crossing frequency of the warp and weft is the same. Twill weaves are available in 2 / 2, 2 / 1, 3 / 1, etc. depending on the frequency of crossing between warp and weft, with 2 / 2 being preferred as it is less susceptible to the load direction. The width of the glass fiber bundles is preferably in the range of 0.3 to 1.2 mm for both warp and weft, as this has a high effect of dispersing force and makes the fabric less likely to unravel. The glass fiber fabric may be further treated with a surface treatment agent as necessary. From the viewpoints of increasing the adhesiveness with the curable resin to be composited and improving the mechanical strength, the glass fiber fabric is preferably treated with a surface treatment agent. The surface treatment agent and the surface treatment method used are not particularly limited and may be any known substance and method. Examples of the surface treatment agent include silane compounds, such as 3-(meth)acryloyloxypropyltrimethoxysilane, 4-(meth)acryloyloxybutyltrimethoxysilane, 5-(meth)acryloyloxypentyltrimethoxysilane, 6-(meth)acryloyloxyhexyltrimethoxysilane, 7-(meth)acryloyloxyheptyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, 9-(meth)acryloyloxynonyltrimethoxysilane, 10-(meth)acryloyloxydecyltrimethoxysilane, 11-(meth)acryloyloxyundecyltrimethoxysilane, Examples of compounds that can be used as surface modifiers for inorganic oxides include silane coupling agents such as 12-(meth)acryloyloxydodecyltrimethoxysilane, 13-(meth)acryloyloxytridecyltrimethoxysilane, 14-(meth)acryloyloxytetradecyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-aminopropylethoxysilane, 3-chloropropyltrimethoxysilane silyl isocyanate, γ-glycidoxypropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, and vinyltrichlorosilane.
[0039] The method for treating the glass fiber fabric with the surface treatment agent is not particularly limited, and examples thereof include a method in which the glass fiber fabric and the surface treatment agent are heated and refluxed in a solvent such as alcohol for several tens of minutes to about 10 hours, preferably for 1 hour to 5 hours, etc. If it is necessary to promote hydrolysis of the surface treatment agent, a method in which water or acidic water such as acetic acid is added to the solvent and heated and refluxed within the above range, the solvent is removed, and the mixture is dried under normal pressure or reduced pressure can be used.
[0040] The amount of the surface treatment agent is usually 0.1 to 10 parts by mass, and preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the glass fiber fabric. The glass fiber fabric after the surface treatment has almost no change in fiber diameter compared to the glass fiber fabric before the treatment.
[0041] The thickness of the glass fiber fabric is usually 0.1 to 0.5 mm, and preferably 0.1 to 0.3 mm. The weight of the glass fiber fabric is, for example, 10 to 790 g / m in the case of plain weave. 2 and preferably 17 to 400 g / m 2 It is. The glass fiber fabric may be commercially available.
[0042] The filling rate of the glass fiber fabric in the composite material for dental cutting of the present invention is usually 48 to 80 mass %, preferably 60 to 78 mass %, and more preferably 70 to 77 mass % of the total amount of the composite material for dental cutting. By setting the content rate of the glass fiber fabric within the above range, the polymerizable monomer-containing composition is impregnated into the gaps between the glass fiber fabrics, and a composite material with sufficient strength can be obtained. Here, the filling rate of the glass fiber fabric can be calculated by cutting a test piece of a predetermined size from the obtained composite material for dental cutting, measuring its mass (pre-mass), and then heat-treating it for a predetermined time using an electric furnace to incinerate the organic components of the composite material for dental cutting, and measuring the mass of the residue (post-mass). In addition, when the glass fiber fabric is treated with a surface treatment agent, the inorganic components of the surface treatment agent that are not incinerated by the heat treatment are strictly included in the filling rate of the glass fiber fabric, but since the inorganic components contained in the surface treatment agent are negligibly small, the filling rate of the glass fiber fabric is hardly changed by the inorganic components contained in the surface treatment agent. At least one glass fiber fabric is sufficient, and the number of sheets is not particularly limited, and two or more sheets can be laminated. For example, the number of glass fiber fabric sheets varies depending on the thickness of the glass fiber fabric, but is usually 1 to 500 sheets, preferably 2 to 300 sheets, and more preferably 3 to 250 sheets.
[0043] The composite material for dental cutting of the present invention may contain, in addition to the above-mentioned components (A) to (C) and glass fiber fabric, the above-mentioned additives (inorganic filler, polymerization accelerator, coloring pigment, opacifier, etc.) within the range that does not impair the effects of the present invention.
[0044] As the color pigment (and opacifier), materials known in general dental treatment can be used to imitate the color tone or transparency of natural teeth. For example, inorganic pigments, organic pigments, etc. are included. Specific examples include iron oxide color pigments, zirconium oxide pigments, titanium white, titanium yellow, etc.
[0045] The dental cutting composite material of the present invention may further contain an inorganic filler as necessary. When an inorganic filler is contained, it is preferable to contain the inorganic filler in the polymerizable monomer-containing composition. The inorganic filler referred to here is different from the glass fiber fabric. The inorganic filler is not particularly limited as long as it is a commonly used inorganic filler, and examples of the inorganic filler include kaolin, talc, quartz, silica (e.g., colloidal silica), alumina, aluminosilicate glass, fluoroaluminosilicate glass, silicon nitride, barium sulfate, calcium phosphate, glass powder, zirconia, and zirconium silicate. The composition, shape, particle size distribution, average particle size, etc. of the inorganic filler are not particularly limited. However, since it is filled in combination with glass fiber fabric, the average particle size is preferably 50 μm or less, more preferably 10 μm or less, and even more preferably 1 μm or less. When an inorganic filler is blended, the inorganic filler can be blended within a range that does not interfere with the effects of the present invention.
[0046] The inorganic filler used in the dental cutting composite material of the present invention is preferably surface-treated. The surface treatment agent and the surface treatment method used are not particularly limited, and may be any known substance and method. Examples of the surface treatment agent include silane compounds, such as 3-(meth)acryloyloxypropyltrimethoxysilane, 4-(meth)acryloyloxybutyltrimethoxysilane, 5-(meth)acryloyloxypentyltrimethoxysilane, 6-(meth)acryloyloxyhexyltrimethoxysilane, 7-(meth)acryloyloxyheptyltrimethoxysilane, 8-(meth)acryloyloxyoctyltrimethoxysilane, 9-(meth)acryloyloxynonyltrimethoxysilane, 10-(meth)acryloyloxydecyltrimethoxysilane, and 11-(meth)acryloyloxyundecyltrimethoxysilane. Examples of compounds that can be used as surface modifiers for inorganic oxides include silane coupling agents such as 12-(meth)acryloyloxydodecyltrimethoxysilane, 13-(meth)acryloyloxytridecyltrimethoxysilane, 14-(meth)acryloyloxytetradecyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, 3-aminopropylethoxysilane, 3-chloropropyltrimethoxysilane silyl isocyanate, γ-glycidoxypropyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, and vinyltrichlorosilane.
[0047] The method for treating the inorganic filler with the surface treatment agent is not particularly limited, and examples thereof include a method in which the inorganic filler and the surface treatment agent are heated and refluxed in a solvent such as alcohol for several tens of minutes to about 10 hours, preferably for 1 hour to 5 hours, etc. If it is necessary to promote the hydrolysis of the surface treatment agent, a method in which water or acidic water such as acetic acid is added to the solvent and heated and refluxed within the above range, the solvent is removed, and the mixture is dried under normal pressure or reduced pressure is also included.
[0048] The amount of the surface treatment agent is usually 0.1 to 50 parts by mass, and preferably 1 to 30 parts by mass, based on 100 parts by mass of the inorganic filler. The inorganic filler after the surface treatment shows almost no change in particle size or particle size distribution compared to the inorganic filler before the treatment. In addition, when the composite material for dental cutting contains an inorganic filler, the filling rate of the glass fiber fabric can be calculated by subtracting the amount of the inorganic filler mixed in from the mass of the residue after incineration (post-mass).
[0049] Manufacturing method of composite material for dental cutting The method for producing the composite material for dental cutting of the present invention (also referred to as a "molded body" or a "cured body") is not particularly limited, and the following methods are possible. For example, the polyfunctional (meth)acrylate polymerizable monomer (A), a low-viscosity polymerizable monomer (B), and a polymerization initiator (C) are mixed to prepare a polymerizable monomer-containing composition, and then the polymerizable monomer-containing composition is impregnated into a glass fiber fabric, followed by polymerization and curing to produce the polyfunctional (meth)acrylate polymerizable monomer. The (A) polyfunctional (meth)acrylate-based polymerizable monomer, the (B) low-viscosity polymerizable monomer, and the (C) polymerization initiator can be mixed using a general mixer such as a stirrer, a disperser, or a kneader.
[0050] Methods for impregnating a glass fiber fabric with a polymerizable monomer-containing composition include, for example, (1) a method in which a glass fiber fabric is placed in a mold having a desired shape in advance, and the polymerizable monomer-containing composition is poured into the glass fiber fabric under normal pressure or while applying pressure, thereby impregnating the glass fiber fabric by utilizing the penetration force (capillary phenomenon, etc.) of the polymerizable monomer-containing composition into the gaps between the glass fiber fabric; and (2) a method in which the glass fiber fabric is immersed in the polymerizable monomer-containing composition, and then pressurized or depressurized, or the polymerizable monomer-containing composition is vigorously sprayed onto the glass fiber fabric, or a roller or brush is used to impregnate the glass fiber fabric with the polymerizable monomer-containing composition. (3) a method of impregnating a glass fiber fabric with a polymerizable monomer-containing composition after reducing its viscosity by heating the polymerizable monomer-containing composition or by heating a mold; (4) a method of impregnating a glass fiber fabric with the polymerizable monomer-containing composition by vacuum suction under reduced pressure and then impregnating and degassing the glass fiber fabric; and (5) a method of immersing a glass fiber fabric in a mold containing the polymerizable monomer-containing composition and impregnating the glass fiber fabric by utilizing the penetrating force of the polymerizable monomer-containing composition between the glass fibers.
[0051] At least one glass fiber fabric can be laminated, preferably two or more. For example, when two or more glass fiber fabrics are laminated, a mold of a desired shape is prepared, a first glass fiber fabric is placed in the mold, a polymerizable monomer-containing composition is poured into the mold, and the glass fiber fabric is impregnated, and a second glass fiber fabric is placed in the mold, and then the polymerizable monomer-containing composition is poured into the mold, so that the glass fiber fabrics are impregnated one by one. When three or more glass fiber fabrics are laminated, the above steps may be repeated a desired number of times. Alternatively, a method may be used in which a plurality of glass fiber fabrics are placed in a mold, a polymerizable monomer-containing composition is poured into the mold, and the fabrics are impregnated all at once. The fiber direction of the second and subsequent sheets may be the same or different from the fiber direction of the first glass fiber fabric. When the directions are different, there is no particular limitation on the direction, and examples thereof include 45 degrees, 90 degrees, and the like. In other words, when two or more layers of glass fiber fabric are laminated and impregnated with the polymerizable monomer-containing composition, each layer of the glass fiber fabric can be impregnated separately, or all layers can be impregnated at once.
[0052] For molding with the mold, for example, a mold and, if necessary, a lid are prepared. The mold has a cavity, and the shape of the cavity is formed into, for example, a prismatic column, a cylindrical column, a square plate, a disk, or the like. The mold may be an assembly type. Specific molds include, for example, a cubic or rectangular parallelepiped shape composed of one bottom plate and four side plates. The cube or rectangular parallelepiped referred to here includes an approximate cube or approximate rectangular parallelepiped, and also includes molds of various shapes. In the above method (1), when the glass fiber fabric is placed in a mold having a prismatic (approximately cubic) cavity with an opening on one side, the glass fiber fabric may be placed so that the surface of the glass fiber fabric faces the opening of the mold, or the cross-sectional portion of the glass fiber fabric faces the opening of the mold. From the viewpoint of improving the filling rate of the glass fiber fabric, it is preferable to place the glass fiber fabric so that the cross-sectional portion faces the opening of the mold.
[0053] In the above method (1), the direction in which the polymerizable monomer-containing composition is poured may be either parallel to the thickness direction of the glass fiber fabric (when there are multiple glass fiber fabrics, this is also called the "lamination direction" or "cross-sectional direction") (perpendicular to the surface of the glass fiber fabric) or perpendicular to the thickness (lamination or cross-sectional) direction (parallel to the surface of the glass fiber fabric), but from the viewpoint of impregnation and degassing efficiency of the polymerizable monomer-containing composition, it is preferable to pour the composition perpendicular to the thickness direction. Here, "parallel" also includes "approximately parallel," and "perpendicular" also includes "approximately perpendicular." Specifically, a glass fiber fabric laminate having a glass fiber fabric with a side length of 100 mm is placed on the bottom surface of a cavity (length 120 mm x width 110 mm x thickness 10 mm) of a mold. It is preferable to stand the glass fiber fabric laminate (the surface of the glass fiber fabric) in such a way that it is parallel to the side surface of the mold (the glass fiber fabric laminate faces sideways) (the upper portion forms an opening), and pour the polymerizable monomer-containing composition from a direction perpendicular to the lamination direction of the glass fiber fabric (above). Thereafter, the glass fiber fabric is placed in a vacuum dryer for 1 to 3 hours to be in a vacuum state, and the polymerizable monomer-containing composition is impregnated into the glass fiber fabric and vacuum degassed. It is preferable to polymerize the glass fiber fabric by retaining it in a blower dryer at 90 to 160°C for 1 to 6 hours. In other words, by pouring the polymerizable monomer-containing composition perpendicular to the lamination direction of the glass fiber fabric and then vacuum degassing, the efficiency of impregnation and vacuum degassing is increased, and a uniformly compounded composite material for dental cutting can be obtained with no air inside.
[0054] The polymerization and curing means is not particularly limited, and can be, for example, produced by a method of heat treatment and / or light irradiation (light irradiation and heat treatment, heat treatment only, or light irradiation only), etc. When polymerization and curing are carried out by light irradiation, it is preferable to carry out heat treatment after light irradiation.
[0055] As a means for polymerizing and hardening by heat treatment, for example, a glass fiber fabric and a polymerizable monomer-containing composition are filled into the hollow portion of a mold (metal, resin, etc.), and then, if necessary, a lid is attached to the mold and the composition is heated under normal pressure or under pressure, whereby the polymerizable monomer-containing composition is polymerized and hardened to obtain a composite material for dental cutting processing.
[0056] The temperature of the heat treatment is appropriately adjusted depending on the composition of the dental cutting composite material and the like, but is usually in the range of 60 to 200°C, for example, preferably 80 to 180°C, and more preferably 90 to 160°C.
[0057] The pressure applied to the composite material for dental cutting during polymerization and hardening is also appropriately adjusted, and is, for example, in the range of normal pressure (atmospheric pressure) to 300 MPa, preferably 10 to 250 MPa, and more preferably 30 to 230 MPa. The temperature and pressure of the heat treatment may be changed over time as necessary.
[0058] When polymerization and curing are carried out by heating under pressure, the thermal polymerization is accelerated, the amount of unpolymerized residual monomer is reduced, and the inclusion of air bubbles is suppressed, resulting in a uniform polymer.
[0059] The means for polymerizing and curing by light irradiation varies depending on the type of photopolymerization initiator, and although ultraviolet light can be used, the polymerizing and curing is usually performed by irradiating visible light that is harmless to the human body. The wavelength of the light is preferably in the range of 250 to 700 nm, and more preferably 300 to 500 nm.
[0060] Examples of light sources that can be used within the above wavelength range include LED lamps, halogen lamps, xenon lamps, metal halide lamps, lasers, fluorescent lamps, and sunlight.
[0061] The irradiation time when the polymerizable monomer is polymerized by irradiating the above-mentioned light varies depending on the thickness, transparency, color tone, and amount of light of the irradiated light of the dental prosthesis or dental cutting composite material obtained from the dental composition, but may be appropriately determined according to the desired polymerization time. The light irradiation is preferably performed for about 10 seconds to 10 minutes, more preferably for 1 minute to 6 minutes.
[0062] A method for producing a dental cutting composite material by polymerization and curing of a dental composition by light irradiation is, for example, to fill a transparent silicone resin or the like with a molding composition, and then irradiate both sides with light having a wavelength of 300 to 500 nm for several minutes to photopolymerize it. Furthermore, in order to increase the degree of polymerization, it is preferable to form a molded body by performing a heat treatment in the range of 90 to 160°C after light irradiation. When two or more layers of glass fiber fabric are laminated, the polymerizable monomer-containing composition may be polymerized and cured for each layer separately, or all layers may be polymerized and cured at once.
[0063] The method for producing a composite material for dental cutting containing a curable resin and a glass fiber fabric of the present invention includes the following steps: (1) placing at least one sheet of woven glass fabric into a mold cavity; (2) impregnating the glass fiber fabric with a polymerizable monomer-containing composition; and (3) A step of polymerizing and curing the polymerizable monomer-containing composition to obtain a composite material for dental cutting containing a curable resin and a glass fiber fabric. It is preferable to have
[0064] The volume of the dental cutting composite material obtained by the above polymerization and hardening is not particularly limited, and is usually 3 cm 3 More than 200cm 3 It is formed in the following range:
[0065] The three-point bending strength of the composite material for dental cutting of the present invention is usually 500 MPa or more, preferably 600 MPa or more, and more preferably 700 MPa or more. By setting the three-point bending strength within the above range, it is possible to prevent a dental prosthesis manufactured from the composite material for dental cutting of the present invention from being fractured by occlusal pressure during clinical use. In consideration of use as a bridge frame (frame material), it is preferable that the lower limit is high. There is no particular limit to the upper limit of the three-point bending strength, and it may be, for example, 2000 MPa or less, preferably 1500 MPa or less, and more preferably 1000 MPa or less. The three-point bending strength can be measured according to JIS T 6517 (hard resin for dental crowns), and will be described in detail in the Examples below.
[0066] The three-point bending elastic modulus of the composite material for dental cutting of the present invention is usually 18 to 36 GPa, preferably 20 to 34 GPa, and more preferably 24 to 32 GPa. By setting the three-point bending elastic modulus within the range of the three-point bending elastic modulus of human tooth dentin (about 18 GPa) and the three-point bending elastic modulus of human tooth enamel (about 84 GPa), which are the abutment teeth for fixing the dental prosthesis made of the composite material for dental cutting, stress concentration during occlusion is unlikely to occur, and the occurrence of breakage of the dental prosthesis, tooth root fracture, etc. can be suppressed. The three-point bending elastic modulus can be measured according to JIS T 6517, and will be described in detail in the examples below.
[0067] Fabrication of dental prostheses The composite material for dental cutting of the present invention can be used by dentists or dental technicians as a dental prosthesis. The composite material for dental cutting of the present invention may be cut manually, but can also be cut by a dental CAD / CAM system (device) or the like to produce (manufacture) a dental prosthesis in the shape of a tooth crown.
[0068] Examples of dental prostheses include dentures, inlays, onlays, crowns, multiple crowns, bridges, fiber cores, and superstructures in implant treatment.
[0069] The composite material for dental cutting of the present invention can be preferably used, in particular, as a frame for a bridge.
[0070] Here, the frame refers to an abutment coping, which is a base that covers an abutment tooth, or a structure in which multiple abutment copings are connected, and the frame is a part whose surface is covered with dental resin, dental porcelain, etc. Therefore, the frame is required to have high strength. The size of the frame is not particularly limited, and is, for example, 5 to 100 mm in length, 5 to 100 mm in width, and 5 to 40 mm in height. The size of the mold is not particularly limited, and is 10 to 150 mm in length, 10 to 150 mm in width, and 5 to 50 mm in height.
[0071] The cutting process is preferably performed using a dental CAD / CAM system (device). As the dental CAD / CAM system (device), a known device can be used. When a dental prosthesis is produced using a CAD / CAM system (device), a high-precision dental prosthesis can be produced more efficiently and in a shorter time than conventional manual work.
[0072] A dental prosthesis obtained from the thus obtained composite material for dental cutting of the present invention has excellent three-point bending strength and a three-point bending modulus close to that of tooth structure. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples, but the technical scope of the present invention is not limited to these examples. The various components, their abbreviations, and test methods used in the examples and comparative examples are as follows.
[0074] (A) Polyfunctional (meth)acrylate-based polymerizable monomer UDMA: 2,2,4-trimethylhexamethylenebis(2-carbamoyloxyethyl)dimethacrylate (NF-501 urethane dimethacrylate, manufactured by Mitsubishi Chemical Corporation, molecular weight: 470.56) Bis-EMA: ethoxylated bisphenol A dimethacrylate (BPE-80N, manufactured by Shin-Nakamura Chemical Co., Ltd., molecular weight: 465.76)
[0075] (B) Low viscosity polymerizable monomer MAA: methacrylic acid (MAA, manufactured by Mitsubishi Chemical Corporation, viscosity: less than 0.3 mPa·s (31°C), molecular weight: 86.09) DEGDM: Diethylene glycol dimethacrylate (2G, Shin-Nakamura Chemical Co., Ltd., viscosity: 3 mPa·s (31°C), molecular weight: 242.27) TEGDM: Triethylene glycol dimethacrylate (3G, Shin-Nakamura Chemical Co., Ltd., viscosity: 5 mPa·s (31°C), molecular weight: 286.32)
[0076] (C) Polymerization initiator BPO: Benzoyl peroxide (Benzoyl peroxide, manufactured by Kishida Chemical Co., Ltd.)
[0077] Glass fiber fabric Glass fiber fabric (1) (ATG26100 treatment tape, manufactured by Sakai Sangyo Co., Ltd.) Single fiber diameter: 9μm Thickness: 0.26mm Mass: 23.9g / m or more Weight: 237g / m 2 Weave: Plain weave Glass fiber fabric (2) (#2116 (silane treatment), manufactured by Alte Cloth Co., Ltd.) Single fiber diameter: 7μm Thickness: 0.1mm Weight: 104g / m 2 Weave: Plain weave
[0078] [Production Example] Example 1 40 parts by mass of component (A) (UDMA), 60 parts by mass of component (B) (MAA), and 0.1 parts by mass of component (C) (BPO) were mixed and stirred with a centrifugal mixer (Thinky Mixer (registered trademark)). A polymerizable monomer-containing composition was obtained. 50 sheets of glass fiber fabric (1) with a side of 100 mm were stacked and placed in the cavity of a mold, and the polymerizable monomer-containing composition was poured into the mold. The mixture was vacuum degassed and impregnated with the polymerizable monomer-containing composition using a vacuum dryer (VOS-451SD, Tokyo Rikakikai Co., Ltd.). The mixture was then polymerized by being held at 150°C for 4 hours in a blower dryer (DRM620TD, Advantec Co., Ltd.) to obtain a composite material for dental cutting containing a curable resin and glass fiber fabric.
[0079] Examples 2 to 23 The components (A), (B), and (C) were mixed in the compounding ratios (parts by mass) shown in Tables 1 to 4 and stirred in a planetary centrifugal mixer (Thinky Mixer (registered trademark), manufactured by Thinky Corporation) to obtain a polymerizable monomer-containing composition. A composite material for dental cutting containing a curable resin and a glass fiber fabric was obtained in the same manner as in Example 1, except that the number of sheets of glass fiber fabric (1) with a side of 100 mm shown in Tables 1 to 4 were laminated.
[0080] Examples 24 to 27 The (A) component, the (B) component, and the (C) component were mixed in the compounding ratio (parts by mass) shown in Table 4 and stirred in a centrifugal mixer (Thinky Mixer (registered trademark), manufactured by Thinky Corporation) to obtain a polymerizable monomer-containing composition. Thereafter, a composite material for dental cutting containing a curable resin and a glass fiber fabric was obtained in the same manner as in Example 1, except that the number of sheets of glass fiber fabric (2) having a side length of 100 mm shown in Table 4 was laminated. Examples 24 and 25 are examples for confirming the reinforcing effect of the glass fiber fabric in many directions, and the conditions such as the types and compounding ratios of the (A) to (C) components, the type of glass fiber fabric, and the number of sheets are the same, and only the way of cutting out the test pieces to be used in the three-point bending test was changed as follows. In Example 25, the test piece was cut out in a direction rotated 90 degrees on a plane from the test piece cut out in Example 24. That is, in Example 24, the test piece was cut out so that the 25 mm length direction of the test piece was the warp direction, and in Example 25, the test piece was cut out so that the 25 mm length direction of the test piece was the weft direction.
[0081] Comparative Example 1 A composite material for dental cutting was produced in the same manner as in Example 1, except that the blending amount of component (A) (UDMA) was 20 parts by mass and the blending amount of component (B) (MAA) was 80 parts by mass. However, because the proportion of component (B) was high, the viscosity of the polymerizable monomer mixture was low, the polymerization shrinkage of the curable resin was large, cracks and exposure of the glass fiber fabric occurred, and the curable resin and the glass fiber fabric were not uniformly composited, so that the intended composite material for dental cutting could not be obtained.
[0082] Comparative Example 2 A composite material for dental cutting was produced in the same manner as in Example 1, except that the blending amount of component (A) (UDMA) was 30 parts by mass and the blending amount of component (B) (MAA) was 70 parts by mass. However, as in Comparative Example 1, the high ratio of component (B) resulted in a low viscosity of the polymerizable monomer mixture, large polymerization shrinkage of the curable resin, cracks and exposure of the glass fiber fabric, and the curable resin and the glass fiber fabric were not uniformly composited, so that the intended composite material for dental cutting could not be obtained.
[0083] Comparative Example 3 A composite material for dental cutting was produced in the same manner as in Example 1, except that the amount of component (A) (UDMA) was 100 parts by mass without adding component (B), and the amount of component (C) (BPO) was 1.5 parts by mass. However, in Comparative Example 3, the viscosity of component (A) was as high as 4300 mPa s, which resulted in insufficient impregnation of the polymerizable monomer-containing composition, resulting in portions of only glass fiber fabric not impregnated with resin, and the curable resin and glass fiber fabric were not uniformly composited, so that the intended composite material for dental cutting was not obtained.
[0084] Comparative Example 4 A composite material for dental cutting was obtained in the same manner as in Example 1, except that the amount of component (A) (Bis-EMA) was 100 parts by mass without adding component (B), and the amount of component (C) (BPO) was 1.5 parts by mass.
[0085] Comparative Example 5 70 parts by mass of component (A) (UDMA), 30 parts by mass of component (B) (MAA), and 0.1 parts by mass of component (C) (BPO) were mixed and stirred in a centrifugal mixer (Thinky Mixer (registered trademark)). A polymerizable monomer-containing composition was obtained. The obtained polymerizable monomer-containing composition was poured into the cavity of a mold and vacuum degassed in a vacuum dryer (VOS-451SD, Tokyo Rikakikai Co., Ltd.). The mixture was then polymerized by retaining it at 150°C for 4 hours in a blower dryer (DRM620TD, Advantec Co., Ltd.) to obtain a dental material that does not contain glass fiber fabric.
[0086] Comparative Example 6 A composite material for dental cutting was obtained in the same manner as in Example 1, except that the amount of component (A) (UDMA) was changed to 70 parts by mass, the amount of component (B) (MAA) was changed to 30 parts by mass, and the number of layers of glass fiber fabric (1) was changed to 16.
[0087] Comparative Example 7 A composite material for dental cutting was produced in the same manner as in Example 1, except that the blending amount of component (A) (UDMA) was changed to 70 parts by mass, the blending amount of component (B) (MAA) was changed to 30 parts by mass, and the number of laminated sheets of glass fiber fabric (1) was changed to 63. However, because the filling rate of the glass fiber fabric was too high, the polymerizable monomer-containing composition was insufficiently impregnated, and there were portions containing only glass fiber fabric, and the curable resin and the glass fiber fabric were not uniformly composited, so that the intended composite material for dental cutting could not be obtained.
[0088] Comparative Example 8 A composite material for dental cutting was produced in the same manner as in Example 1, except that the blending amount of component (A) (UDMA) was 70 parts by mass, the blending amount of component (B) (MAA) was 30 parts by mass, and component (C) (BPO) was not blended. However, the polymerizable monomer-containing composition did not harden, and the intended composite material for dental cutting was not obtained.
[0089] Comparative Example 9 A composite material for dental cutting was produced in the same manner as in Example 1, except that the blending amount of component (A) (UDMA) was 70 parts by mass, the blending amount of component (B) (MAA) was 30 parts by mass, and the blending amount of component (C) (BPO) was 6 parts by mass. However, since component (C) (BPO) was not dissolved in the monomers (component (A) and component (B)), the intended composite material for dental cutting could not be obtained. Therefore, in Comparative Examples 1 to 3 and 7 to 9 in which the desired composite materials were not obtained, the three-point bending test and the measurement of the filling rate of the glass fiber fabric were not performed.
[0090] Reference examples 1~2 In Reference Examples 1 and 2, commercially available dental cutting composite materials containing a curable resin and a glass fiber fabric were used. Reference Example 1 is Trinia (Bicon, block type, 40 mm x 19 mm x 15 mm, (hereinafter referred to as commercially available product A)). Reference Example 2 is Cabo C-Temp Blank (Cabo Dental, for Everest, 42 mm x 20 mm x 20 mm, (hereinafter referred to as commercially available product B)).
[0091] Test Method [Viscosity of polymerizable monomer mixture] In Examples 1 to 12 and Comparative Examples 1 to 4, the components (A) and (B) were mixed separately to produce a polymerizable monomer mixture, and the viscosity of the mixture was measured using an SV-type (tuning fork vibration type) viscometer (SV-1A, manufactured by A&D Co., Ltd.) at a natural frequency of 30 Hz and a measurement temperature of 31° C. However, for polymerizable monomer mixtures with a viscosity of more than 1000 mPa·s, the viscosity was measured using a B-type (rotational type) viscometer (digital B-type viscometer LVT, manufactured by Eiko Seiki Co., Ltd.) at a rotation speed of 60 rpm and a measurement temperature of 31° C. (JIS Z 8803). Each measurement was performed once, and the measured value was regarded as the viscosity of the polymerizable monomer mixture.
[0092] [Filling rate of glass fiber fabric] From the composite materials for dental cutting obtained in Examples 6 and 13 to 27, Comparative Example 6, and Reference Examples 1 to 2, test pieces of 2 mm x 2 mm x 25 mm were prepared by cutting, and the mass (pre-mass) was measured, and then the materials were heat-treated at 500 ° C. for 1 hour using an electric furnace, and the mass of the residue (post-mass) was measured. Since the curable resin disappears by heat treatment and the glass fiber fabric remains, the filling rate of the glass fiber fabric was calculated from the ratio of the mass obtained by subtracting the post-mass from the pre-mass and the pre-mass. Note that the glass fiber fabric used was surface-treated with a surface treatment agent, and the surface treatment agent contains inorganic components, but the amount of the surface treatment agent is very small, and the inorganic components remaining after heat treatment are even smaller and negligible, so there is no problem in calculating the filling rate of the glass fiber fabric by the above method. The test pieces were cut so that the 25 mm length of the test pieces was in the direction of the warp, except for the composite material for dental cutting obtained in Example 25. Only the composite material for dental cutting obtained in Example 25 was cut so that the 25 mm length of the test piece was in the direction of the weft. In each Example, 10 test pieces were prepared, and the average value of the 10 measurements was taken as the filling rate of the glass fiber fabric.
[0093] [Three-point bending test] The three-point bending test was performed according to the test method of JIS T 6517, and the three-point bending strength and three-point bending modulus were measured. From the composite materials for dental cutting obtained in Examples 1 to 27, Comparative Examples 4 to 6, and Reference Examples 1 to 2, test pieces of 2 mm x 2 mm x 25 mm were cut out using a diamond cutting wheel on a precision cutting machine, and the surfaces of the test pieces were polished with waterproof abrasive paper (P2500), and then immersed in distilled water at 37 ° C. for 24 hours. A three-point bending test was performed using a small universal testing machine (EZ-Graph, manufactured by Shimadzu Corporation) under conditions of a crosshead speed of 1 mm / min and a support distance of 20 mm, and the three-point bending modulus was obtained from the slope of 25% to 50% of the maximum test force (N) in the stress displacement curve during the measurement of the three-point bending strength. The test pieces were cut so that the 25 mm length direction of the test pieces was the direction of the warp, except for the composite material for dental cutting obtained in Example 25. Only the composite material for dental cutting obtained in Example 25 was cut so that the 25 mm length of the test piece was in the direction of the weft. In each Example, five test pieces were prepared, and the average values of the five measurements were used as the three-point bending strength and three-point bending modulus.
[0094] For the composite materials for dental cutting of Examples 1 to 27, Comparative Examples 1 to 9, and Reference Examples 1 and 2, the compounding ratios of components (A), (B), and (C), the type, number of layers, and filling rate of the glass fiber fabric, as well as the viscosity, three-point bending strength, and three-point bending modulus of the polymerizable monomer mixture are shown in Tables 1 to 4.
[0095] [Table 1]
[0096] [Table 2]
[0097] [Table 3]
[0098] [Table 4]
[0099] In Examples 1 to 27, the viscosity of the polymerizable monomer mixture at 31° C. was 10 to 2300 mPa s, so that a composite material for dental cutting was obtained in which a curable resin and a glass fiber fabric were combined. The composite materials for dental cutting obtained all had a glass fiber fabric filling rate in the range of 48 to 80 mass%, a three-point bending strength of 500 MPa or more, and a three-point bending modulus of elasticity of 18 to 36 GPa. In Examples 24 and 25, the test pieces were cut out in the warp direction and the weft direction of the glass fiber fabric, and the test pieces were subjected to the three-point bending test. The three-point bending strength and three-point bending modulus were all close to each other, and both were excellent. This shows that the composite material for dental cutting of the present invention using the glass fiber fabric can obtain a reinforcing effect in multiple directions. In Comparative Examples 1 and 2, the viscosity of the polymerizable monomer mixture was low and the polymerization shrinkage of the curable resin was large, resulting in cracks and exposure of the glass fiber fabric, and the curable resin and the glass fiber fabric were not uniformly combined, so that the desired composite material for dental cutting could not be obtained. In Comparative Example 3, the polymerizable monomer mixture did not contain component (B), and the viscosity of component (A) was as high as 4,300 mPa s, which resulted in poor impregnation and a failure to uniformly combine the curable resin and the glass fiber fabric. As a result, the desired composite material for dental cutting was not obtained. In Comparative Example 4, the viscosity of component (A) (511 mPa s) was lower than in Comparative Example 3, and the polymerizable monomer-containing mixture was sufficiently impregnated into the glass fiber fabric, resulting in a uniform composite. However, the polymerizable monomer mixture did not contain component (B), and the flexural strength of the resulting composite material was 373 MPa, not reaching 500 MPa. This is thought to be because component (B) has the effect of increasing the polymerization rate during curing due to its short molecules, but since Comparative Example 4 does not contain component (B), the polymerization rate was low, and sufficient strength was not obtained. In Comparative Example 5, since no glass fiber fabric was included, the flexural strength of the obtained curable resin was 192 MPa, which did not reach 500 MPa. In Comparative Example 6, the filling rate of the glass fiber fabric was 40 mass%, which was lower than 48 mass%, so the bending strength of the obtained composite material was 477 MPa, which did not reach 500 MPa, and the three-point bending modulus was 15 GPa, which did not reach 18 GPa. In Comparative Example 7, the filling rate of the glass fiber fabric was too high, resulting in insufficient impregnation of the polymerizable monomer-containing composition, resulting in areas of only glass fiber fabric, and the curable resin and glass fiber fabric were not uniformly combined, so that the desired composite material for dental cutting could not be obtained. In Comparative Example 8, the polymerizable monomer mixture did not contain the polymerization initiator (C) and did not harden, so that the intended composite material for dental cutting was not obtained. In Comparative Example 9, the amount of (C) polymerization initiator was too large, resulting in undissolved (C) component remaining in the polymerizable monomer mixture, and the curable resin and glass fiber fabric were not uniformly combined, so that the desired composite material for dental cutting was not obtained. [Industrial Applicability]
[0100] The composite material for dental cutting of the present invention can be cut using a dental CAD / CAM system, and can provide a dental prosthesis (dental frame) having excellent three-point bending strength and a three-point bending modulus close to that of tooth structure.
Claims
1. A dental cutting composite material for use in a CAD / CAM system, comprising a hardenable resin and a glass fiber fabric, The curable resin is (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator A polymerizable monomer-containing composition comprising the above is polymerized and cured, The polymerizable monomer-containing composition does not contain a filler or an inorganic powder, The content of the polyfunctional (meth)acrylate polymerizable monomer (A) contained in the polymerizable monomer-containing composition is 40 to 95 mass %, The content of the low-viscosity polymerizable monomer (B) is 5 to 150 parts by mass relative to 100 parts by mass of the polyfunctional (meth)acrylate polymerizable monomer (A), The content of the polymerization initiator (C) is 0.002 to 5 parts by mass with respect to 100 parts by mass in total of the polyfunctional (meth)acrylate polymerizable monomer (A) and the low-viscosity polymerizable monomer (B), The (B) low-viscosity polymerizable monomer is a polymerizable monomer having a viscosity of 5 mPa·s or less at 31° C., The viscosity of the mixture of the polyfunctional (meth)acrylate polymerizable monomer (A) and the low-viscosity polymerizable monomer (B) at 31° C. is 8 to 2300 mPa·s, and A composite material for dental cutting used in a CAD / CAM system, wherein the filling rate of the glass fiber fabric in the composite material for dental cutting is 48 to 80 mass %.
2. A composite material for dental cutting processing used in the CAD / CAM system described in claim 1, wherein the filling rate of the glass fiber fabric in the composite material for dental cutting processing is 57 to 80 mass %.
3. A composite material for dental cutting processing used in the CAD / CAM system described in claim 2, wherein the content of the (C) polymerization initiator is 0.002 to 1 part by mass per 100 parts by mass of the total of the (A) polyfunctional (meth)acrylate polymerizable monomer and the (B) low viscosity polymerizable monomer.
4. 4. The composite material for dental cutting used in a CAD / CAM system according to claim 3, having a three-point bending strength of 674 MPa or more.
5. 2. The composite material for dental cutting used in a CAD / CAM system according to claim 1, having a three-point bending modulus of elasticity of 18 to 36 GPa.
6. The composite material for dental cutting used in the CAD / CAM system according to claim 1, wherein the (A) polyfunctional (meth)acrylate polymerizable monomer comprises at least one selected from the group consisting of a di(meth)acrylate containing bisphenol A, a urethane di(meth)acrylate which is a reaction product of 2 moles of a (meth)acrylate having a hydroxyl group and 1 mole of a diisocyanate, a tri(meth)acrylate, and a tetra(meth)acrylate.
7. 2. A composite material for dental cutting used in a CAD / CAM system as described in claim 1, wherein the (B) low viscosity polymerizable monomer comprises at least one selected from the group consisting of methacrylic acid, diethylene glycol dimethacrylate, and triethylene glycol dimethacrylate.
8. 2. A composite material for dental cutting used in the CAD / CAM system according to claim 1, which is used as a frame.
9. The dental cutting composite material comprises: (A) a polyfunctional (meth)acrylate polymerizable monomer, (B) a low viscosity polymerizable monomer, and (C) Polymerization initiator 2. The composite material for dental cutting used in a CAD / CAM system according to claim 1, which is a glass fiber fabric impregnated with a polymerizable monomer-containing composition comprising the above and polymerized and cured.
Citation Information
Patent Citations
Method and instrument for measuring strain of concrete structure
JP1984044602A
Method for producing dental material and prosthetic material for dental use
JP2002104914A
Dental material and dental prosthesis
JP2003104822A
Method for preparing dental composite resin material and preparations therefrom
JP2018521963A
Dental mill blank
WO2020166667A1